Vite de' più eccelenti pittori scultori e architetti - Vasari, Giorgio 1511-1574 (Siena Pazzini Carli, 1791)
'The Lives of the Most Excellent Painters, Sculptors, and Architects,' often simply known as 'The Lives,' is a series of artist biographies written by 16th-century Italian painter and architect Giorgio Vasari, which is considered perhaps the most famous, and even today the most-read work of the older literature of art, some of the Italian Renaissance's most influential writing on art, and the first important book on art history.
Vol. 1 frontispiece is folded page with engraved portrait of Vasari by G. B. Leonetti after G. Cades.
Every biography is preceded by a plate with engraved portrait
Originally published in 1550 and 1568
Keywords: 16th Century (1501-1600); Fine art; Biography; Italy